Music Scenes, Space and the Body. (March 2015) - Driver, Christopher; Bennett, Andy
The concept of scene is now a primary conceptual framework for studying the production and consumption of popular music. In a formative essay, Straw (1991) offered the important observation that scene could be theorized as both a local and trans-local phenomenon. Peterson and Bennett (2004) have added a new dimension to this conceptualization of music scenes through positing virtuality as a further medium for scene involvement. Missing from each element of this tripartite model of scene – local, trans-local, and virtual – is any consideration of how music scenes are enacted through the process of embodiment. In this article, we argue that embodiment is critically important for how music scenes are constructed, enacted and maintained by participants. The corporeal element of scene introduced through its embodiment by social actors, we argue, is key to our understanding of the music scene as an anchoring place within everyday urban, regional and, increasingly, rural landscapes.